P096 QUALITY OF LIFE FOLLOWING ROBOTIC-ASSISTED RETROMUSCULAR VENTRAL HERNIA REPAIR. (25th November 2021) - Valsamidis, Alexandros; Frederichsen, Mathias; Nielsen, Kristian Als; Harthimmer, Mads; Helligsø, Per; Nielsen, Michael
Abstract: Aim: Robotic-assisted ventral hernia repair (rVHR) has emerged as an alternative to current open and laparoscopic procedures. The present study aims to determine the effect of rVHR on postoperative quality of life. Material and Methods: Patients undergoing elective rVHR from 01/01 2017 until 12/6 2020 were identified from the hospitaĺs electronic medical record system. Patient demographic, clinical presentation, location of the hernial defect and postoperative complications were obtained from the case notes. A phone interview was also conducted to assess postoperative life quality using the EuraHS-QoL questionnaire. The pre and postoperative life quality assessment was performed to determine the effect of robotic-assisted ventral hernia repair on 1. Pain at the site of the hernia, 2. Restrictions of activities due to pain or discomfort at the site of the hernia and 3. Esthetical discomfort. Moreover, patients were asked whether they felt their overall quality of life had improved, deteriorated or was unaltered after the procedure. A Wilcoxon signed rank test was conducted to determine the effect of the repair on postoperative life quality. Results: 85 out of 99 patients completed the interview and were included in this case series. The survey revealed a highly significant improvement of life quality in all categories (P < 0. 01). 86% of the participants reported that their overall quality of life had improved, 13% reported no change and 1% felt that it had deteriorated. Conclusions: Robotic-assisted retromuscular ventral hernia repair is a safe procedure that is associated with a significant improvement of patient quality of life.